On-surface synthesis of super-heptazethrene. Issue 54 (4th June 2020) - Mishra, Shantanu; Melidonie, Jason; Eimre, Kristjan; Obermann, Sebastian; Gröning, Oliver; Pignedoli, Carlo A.; Ruffieux, Pascal; Feng, Xinliang; Fasel, Roman
Abstract : On-surface synthesis of a zethrene compound, super-heptazethrene, is reported on Au(111), along with its detailed characterization using scanning tunneling microscopy. Abstract : Zethrenes are model diradicaloids with potential applications in spintronics and optoelectronics. Despite a rich chemistry in solution, on-surface synthesis of zethrenes has never been demonstrated. We report the on-surface synthesis of super-heptazethrene on Au(111). Scanning tunneling spectroscopy investigations reveal that super-heptazethrene exhibits an exceedingly low HOMO–LUMO gap of 230 meV and, in contrast to its open-shell singlet ground state in the solution phase and in the solid-state, likely adopts a closed-shell ground state on Au(111).